Akibat Hukum Perkawinan yang Salah Satu Pihak Berpindah Agama Pasca Perkawinan ditinjau dari Undang-undang No.16 Tahun 2019 tentang Perubahan Atas Undang-undang No.1 Tahun 1974 tentang Perkawinan dan Kompilasi Hukum Islam - Salma Aisha Rahmat; Husni Syawali (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. In Islamic law the marital status is Faskh or damaged and this is also reinforced by the MUIFatwa. Meanwhile, regarding the legal consequences of religious conversion on child custody, if itrefers to Islamic law, the Muslim party has the right to take care of his child if one of the husband andwife is an infidel. However, in the Decision of Case Number 0117/Pdt.G/2016/PA.Prgi, the child whois the object of the dispute falls his custody (hadhanah) to his apostate mother. The Panel of Judgesbased their argument on the application of the legal principle regarding